Assam Development Report - Planning Commission (Planning Commission, 1950)
The most striking fact of Assam’s economic development is that it is falling behind the rest of the country. In 1950-51, per capita income in Assam was 4 per cent above national average. In 1998-99 it was 41 per cent below the national average at current prices and 45 per cent below the national average at 1980-81 prices. What is even more alarming is that the gap is growing. Between 1980 and 1990, per capita income at 1980-81 prices grew by 20 per cent in Assam compared with 40 per cent for all-India. Between 1980 and 1998, per capita income in Assam grew by 10 per cent compared with 39 per cent for all India.
Planning Commission Government of India
Planning Commission Government of India